BUSINESS ETHICS AND GOOD CORPORATE GOVERNANCE IN RELEVANCE IMPLEMENTATION OF THE COMPANY'S SOCIAL RESPONSIBILITY - Judiatin Rachmiarti Kusumah (Dinasti Publisher, 2020)
The challenges for companies are getting bigger today. CSR is used as a guideline for corporate strategy to take the interests of all stakeholders into account. The application of CSR has to do with how the company is well managed and managed (GCG). The implementation of GCG has a positive effect on the business environment of a company and has a positive effect on the company as investors increasingly trust the company. CSR develops because the long-term sustainability of the company is more important than just profitability. Companies have social and ecological responsibility for ethical behavior, which is referred to as corporate social responsibility (CSR) or corporate citizenship. Corporate Social Responsibility (CSR) is a company's commitment to the conduct of its business. It aims not only to increase the company's financial profit, but also to build a sustainable socio-economy. It can be concluded that the fundamental aspect of implementing CSR for the company is a form of the company's commitment to the well-being of employees and their families, the surrounding community (local) and in particular the entire community and that the implementation takes place in a sustainable manner. This paper is intended to provide an overview of the implementation of corporate social responsibility with its relevance to business ethics and good corporate governance in Indonesia. The research method used is a library and observation method based on the author's experience in dealing with PT XYZ Raya, one of the national companies for paints and chemicals, as a supplier of various types of colors